Experiences in Open Research & Education for Sustainable Development in Africa - Abukutsa-Onyango, Mary (My University, 2019)
Presentation of my research to promote Sustainable Production and Utilization of African Indigenous Vegetables (AIVs) for Nutrition Security and Poverty Reduction in Kenya (Africa).
Keywords: African Indigenous vegetables; Open science; Food security